IDENTIFIKASI LOKASI PANGKALAN OJEK KABUPATEN KENDAL BERBASIS WEB GIS (Information Technology and Telematics, 2014)
Abstract Geographical conditions Kendal district consists of mountains, hills and plains that operate public transport apparently do not reach up to the village level and not oprasinya time to 24 hours, with the condition of the people often use a motorcycle taxi service to deliver the place of destination. The purpose of this study is to make the application of GIS base location motorcycles in Kendal district melelui Accessible web, so help and facilitate the public to know the location of the nearest base and facilitate a motorcycle when the motorcycle taxi service will use. The results of this research is the application of geographic information system base locations motorcycle Kendal district by utilizing a web-based service google maps as the map server and Mozilla Firefox as a web browser, for media storage using a MySQL database. Keywords: Web GIS, the location of the base motorcycle Kendal, identification